Research of globalization’s interrupted character in context of social development and global security. Part 1. Analysis of pre-crisis period (up to second half of 2008) - Zgurovsky, A. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2009)
In given research we introduce the new valuating method of globalization in scope of basic social development and global security indicators, further named as SDS. By implementing the well-known KOF and newly introduced SDS methods the comparative analysis of globalization level among different states is carried out. With the help of Principal Compound Analysis there is a reduction in the number of variables that determine characteristics of globalization to particular factors and their simplified representation of dependence on globalization level. Запропоновано методику оцінки рівня глобалізації країн світу в просторі головних вимірів (індикаторів) їх соціального розвитку та безпеки, названу методикою МСРБ. Із використанням відомої методики КОF та запропонованої МСРБ проведено порівняльний аналіз рівня глобалізації різних країн світу. За допомогою методу Principal Compound Analysis виконано редукцію кількості змінних, які визначають властивості глобалізації щодо деяких характерних чинників, та здійснено спрощене представлення залежності рівня глобалізації від виявлених найсуттєвіших чинників. Предложена методика оценки уровня глобализации стран мира в пространстве главных измерений (индикаторов) их социального развития и безопасности, назван ная методикой МСРБ. С использованием известной методики КОF и предложенной МСРБ проведен сравнительный анализ уровня глобализации разных стран мира. С помощью метода Principal Compound Analysis произведена редукция количества переменных, которые определяют свойства глобализации по отношению к некоторым характерным факторам, и осуществлено упрощенное представление зависимости уровня глобализации от выявленных самых существенных факторов.